A Universal Approach for the Non‐Iterative Parametrization of Near‐Surface Turbulent Fluxes in Climate and Weather Prediction Models. (4th August 2021) - Gryanik, V. M.; Lüpkes, C.; Sidorenko, D.; Grachev, A.
Abstract: Weather prediction and climate simulations need reliable parameterizations of turbulent fluxes in the stable surface layer. Especially in these conditions, the uncertainties of such parametrizations are still large. Most of them rely on the Monin‐Obukhov similarity theory (MOST), for which universal stability functions (SFs) represent important ingredients. The SFs are nonlinear, if so, a numerical iteration of the MOST equations is required. Moreover, presently available SFs are significantly different at large stability. To simplify the calculations, a non‐iterative parametrization of fluxes is derived and corresponding bulk transfer coefficients for momentum and heat for a package of five pairs of state‐of‐the‐art SFs are proposed. For the first time, a parametrization of the related transfer coefficients is derived in a universal framework for all package members. The new parametrizations provide a basis for a cheap systematic study of the impact of surface layer turbulent fluxes in weather prediction and climate models. Plain Language Summary: Results of weather forecast, present‐day climate simulations, and future climate projections depend among other factors on the interaction between the atmosphere and the underlying sea‐ice, the land, and the ocean. In numerical weather prediction and climate models, some of these interactions are accounted for by transport coefficients describing the turbulent exchange of momentum, heat, and humidity. Currently used transfer coefficients have, however, large uncertainties in flow regimes being typical for cold nights and seasons, but especially in the polar regions. Furthermore, their determination is numerically complex. It is obvious that progress could be achieved when the transfer coefficients would be given by simple mathematical formula in frames of an economic computational scheme. Such a new universal, so‐called non‐iterative parametrization scheme is derived for a package of transfer coefficients. The derivation is based on the Monin‐Obukhov similarity theory, which is well accepted in the scientific community. The new scheme provides a basis for a cheap systematic study of the impact of near‐surface turbulence and of the related transports of momentum, heat, and humidity in models. Key Points: A non‐iterative universal parameterization of surface layer turbulent fluxes is derived using Monin‐Obukhov similarity theory Bulk transfer coefficients are given, which are based on five pairs of state‐of‐the‐art surface layer stability functions The new parametrizations provide a basis for a cheap study of the impact of surface layer turbulent fluxes in numerical weather prediction and climate models